(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate parameters indicative of sperm quality of fresh and post-thawed semen of Aberdeen Angus, Holstein and Nelore bulls. Thirty-nine bulls were used: Aberdeen Angus (n=13), Holstein (n=13) and Nelore (n=13). The ejaculate collects were performed twice a week using artificial vagina, totaling 792 semen collections, 307 for Aberdeen Angus, 225 for Holstein and 260 for Nelore bulls. After collection, fresh semen was evaluated and semen freezing was performed. After freezing, the batches were thawed and progressive motility was determined. The analysis of fresh semen showed that there was no difference (P = 0.053) between the Aberdeen Angus and Nelore breeds, while ejaculates from Holstein bulls showed a statistical difference (P = 0.024). As well, a difference (P<0.001) was identified in the sperm concentration of the three breeds. In the samples evaluated after thawing, a statistical difference was observed between Holstein and Nelore breeds (P<0.001), while the values of the Angus breed were similar to the other two breeds. The difference in motility of fresh and post-thawing semen showed that Nelore and Angus bulls showed greater variation in values between the analyzes (26.0±8.9% and 25.3±8.4%, respectively) showing a significant difference (P<0.001) in relation to Holstein bulls (20.6±9.3%) that obtained the smallest difference. The analysis of fresh and post-thawing semen did not show any significant difference (P=0.13) between breeds. In conclusion, the semen cryopreservation process causes a decrease in the physical parameters of the semen and these quality losses suffer interference according to the breeds.